Optical Fiber Communication Conference (OFC) 2019 2019
DOI: 10.1364/ofc.2019.m2e.1
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial of Machine-Learning-Assisted and SDN-Based Optical Network Management

Abstract: In this paper, we reported machine-learning based network dynamic abstraction over a field-trial testbed. The implemented network-scale NCMDB allows the ML-based quality-of-transmission predictor abstract dynamic link parameters for further network planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The ANN-based OSNR prediction were evaluated over a field-trial testbed [18]. The results showed that ANN-based regression model achieved a high accuracy that the mean square error (MSE) is less than 1 dB.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The ANN-based OSNR prediction were evaluated over a field-trial testbed [18]. The results showed that ANN-based regression model achieved a high accuracy that the mean square error (MSE) is less than 1 dB.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, most of the works mentioned above focused on QoT estimation of single channel, the relevant algorithms have achieved high accuracy for both classification and regression. For example, most of ML-based regression models for OSNR or Q-factor predictions in [18][19][20][21] have achieved the high accuracy for a single channel within at most 1 dB and down to 0.02 dB error, however, the real scenarios of optical systems are generally multi-channel transmission systems. The physical parameters of optical opponents have not been considered in most cases, these physical parameters like EDFA parameters have deep influence on the performance of transmissions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, failure to handle dynamics in optical device will lead to inaccuracy of QoT estimations in long term. In [15,16,21], we built a cloud network configuration and optical performance monitoring database to collect the physical parameters over the whole network. ANN-based QoT prediction was developed to predict a single channel.…”
Section: Literature Review Of Network Abstraction With Machine Learnimentioning
confidence: 99%
“…In [21], Gaussian process regression is used to estimate the optical signal-noise-ration (OSNR) of the link, and the mean-square error (MSE) is only 0.7 dB. In [22], an artificial neural network (ANN) is utilized to predict the OSNR. As a novel planning framework, this ML-based prediction tool and the software-defined network (SDN) controller are cooperated to adapt the actual network states.…”
Section: The Reduction Of Design Marginsmentioning
confidence: 99%